Cover Image. (8th December 2022) - Wu, Alex; Brider, Jason; Busch, Florian A.; Chen, Min; Chenu, Karine; Clarke, Victoria C.; Collins, Brian; Ermakova, Maria; Evans, John R.; Farquhar, Graham D.; Forster, Britta; Furbank, Robert T.; et al.
Abstract : The cover image is based on the Original Article A cross‐scale analysis to understand and quantify the effects of photosynthetic enhancement on crop growth and yield across environments by Alex Wu et al., https://doi.org/10.1111/pce.14453 .